Mechanical and electrical properties of Bi1.5-xLaxZn0.92Nb1.5O6.92 pyrochlore ceramics - GENÇ, SEVAL (SPRINGER, 2016)
The physical properties of Bi1.5-xLaxZn0.92Nb1.5O6.92 solid solutions are investigated by means of X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersion X-ray spectroscopy (EDS), and temperature dependent relative permittivity and electrical resistivity measurements. The La content which was varied from 0.10 to 0.60 is found to be solvable up to 0.21. Further increase in the amount of the La content caused the appearance of Bi0.4La0.6O1.5, LaNbO4, and ZnO minor phases in the pyrochlore matrix. While the lattice parameter and the theoretical, bulk and relative density are hardly affected by the increase in the La content, the strain, the dislocation density and the crystallite size are remarkably varied. The relative permittivity and temperature coefficient of relative permittivity are found to be sensitive to the La-Content. The electrical resistivity is observed to be temperature invariant below 390 K. It exhibits an insulator-semiconductor transition property at a critical temperature that increases with the increasing La content. Such observation is assigned to the increase in the dislocation density, which arises from the increment in the La content. The activation energies of the doped ceramics, which are determined from the electrical resistivity analysis are found to be similar to 1.12-1.00 eV.
Keywords: Pyrochlore structure; La-doping; Microwave ceramics; BZN CERAMICS